2011
DOI: 10.1007/s00380-010-0114-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of ischemia-modified albumin in estimating the extent and scope of cardiac ischemia in patients with ST elevation myocardial infarction

Abstract: Ischemia-modified albumin (IMA) is a laboratory biomarker of cardiac ischemia. Our study aims to determine whether IMA can estimate or represent to any degree the extent of myocardial ischemia. We expect that the higher the marker of cardiac necrosis (maximum value after serial measurements) the greater the preceding cardiac ischemia, indicated by IMA in patients diagnosed with STEMI prior to direct percutaneous coronary intervention (PCI). We studied 216 patients indicated for direct PCI with a diagnosis of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…CuSO 4 exposure significantly increased the plasma levels of inflammatory cytokines, including IMA, hFABP, cTn-I, and BNP, which are strongly associated with increased risks of myocardial injury and ischemia. It is well known that IMA has been evaluated as a potential biomarker of early myocardial ischemia in clinical models of heart injury recognized by the United States Food and Drug Administration [ 34 , 35 ]; hFABP is a specific biomarker and immediately functions as a myocardial fatty acid transporter when myocardial injury occurs [ 36 ]; cTn-I, a specific contractile protein on the myocardial fibers, is a non-enzymatic serum marker for detecting myocardial injury with high specificity and sensitivity [ 37 ]; and BNP is a validated risk marker in cardiac diseases and can provide a remarkable guidance in cardiovascular complications prediction [ 38 ]; HO-1, a crucial part of the Nrf2/HO-1 signaling pathway, plays a physiological role through its anti-inflammatory and anti-oxidant actions [ 19 , 39 ]. In previous studies, HO-1 up-regulation decreased myocardial ischemia-reperfusion injury and effectively promoted the recovery of cardiac function through the activation of the Nrf2/HO-1 pathway [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…CuSO 4 exposure significantly increased the plasma levels of inflammatory cytokines, including IMA, hFABP, cTn-I, and BNP, which are strongly associated with increased risks of myocardial injury and ischemia. It is well known that IMA has been evaluated as a potential biomarker of early myocardial ischemia in clinical models of heart injury recognized by the United States Food and Drug Administration [ 34 , 35 ]; hFABP is a specific biomarker and immediately functions as a myocardial fatty acid transporter when myocardial injury occurs [ 36 ]; cTn-I, a specific contractile protein on the myocardial fibers, is a non-enzymatic serum marker for detecting myocardial injury with high specificity and sensitivity [ 37 ]; and BNP is a validated risk marker in cardiac diseases and can provide a remarkable guidance in cardiovascular complications prediction [ 38 ]; HO-1, a crucial part of the Nrf2/HO-1 signaling pathway, plays a physiological role through its anti-inflammatory and anti-oxidant actions [ 19 , 39 ]. In previous studies, HO-1 up-regulation decreased myocardial ischemia-reperfusion injury and effectively promoted the recovery of cardiac function through the activation of the Nrf2/HO-1 pathway [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that IMA levels, when combined with electrocardiographic findings, troponin, and CK-MB levels, help diagnose MI with high sensitivity and high specificity in patients admitted to the emergency department with chest pain [9][10][11] . It has also been shown that higher IMA levels are associated with the extent of ischemia 17 , left ventricular systolic dysfunction in patients with STEMI treated with primary PCI 18 , and with major cardiac adverse events in NSTEMI patients 19 . Ischemia-modified albumin has been introduced as a novel diagnostic marker for acute coronary ischemia 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-modified albumin (IMA) is a novel marker for assessing tissue ischemia. IMA levels correlate to tissue ischemia [3,4]. In this study, we expected that microvascular thrombosis caused by OHSS might elevate serum IMA levels that could alert clinicians of severe complications.…”
Section: Introductionmentioning
confidence: 94%